Effects of Organic Fertilizer Replacing Some Nitrogen Fertilizers on the Structure and Diversity of Inter-Root Soil Fungal Communities in Potato - Songhu Chen; Zhenhua Zhao; Xinyuan Hu; Bo Dong; Pingliang Zhang; Xiaowei Liu; Kuizhong Xie; Dandan Du; Xiaohua Sun; Jiaying Ma; Jinyu Li; Xiaoyan Ren (Agronomy)
The aim of this study was to investigate the effects of organic fertilizer replacing part of the nitrogen fertilizers on the structure and diversity of the inter-root soil fungal communities of potatoes. By carrying out a field trial in Gaoquan Village, Tuanjie Town, Dingxi City, Gansu Province, the main potato-producing area in China, the optimal proportion of organic fertilizer to replace nitrogen fertilizer was determined to provide a scientific basis for the rational use of organic fertilizer to improve the structure and function of soil fungal communities. The experiment was laid out with six treatments: CK (no nitrogen fertilizer, phosphate and potash fertilizer applied), CF (nitrogen fertilizer alone, control), T1 (25% replacement of nitrogen fertilizer), T2 (50% replacement of nitrogen fertilizer), T3 (75% replacement of nitrogen fertilizer), and T4 (100% replacement of nitrogen fertilizer). A systematic study of the inter-root soil fungal community structure, diversity, and soil physicochemical properties during potato harvesting was conducted using high-throughput sequencing technology. The results show that the organic fertilizer replacing part of the nitrogen fertilizer significantly increased the content of alkaline dissolved nitrogen, quick-acting potassium, quick-acting phosphorus, and organic matter in the inter-root soil of the potatoes, and significantly reduced the pH value of the soil. There was a trend of decreasing soil fungal abundance and a significant decrease in the Alpha diversity of the soil fungi. The treatment groups in the soil had as their core fungi Acomycota, Mortierellomycota, Basidiomycota, and others. The organic fertilizers replacing the nitrogen fertilizers significantly altered the structural composition of the inter-root soil fungal community of the potatoes, and increased the differential fungi in the soil. The number of functionally diverse and complex fungi in the soil gradually increased, and the function of the fungal community gradually changed from Singularity to diversification and complexity. A redundancy analysis showed that the soil pH was the main environmental factor affecting the inter-root soil fungal communities of potatoes under organic fertilizer replacing N fertilizer.